Multiple concurrent and convergent stages of genome reduction in bacterial symbionts across a stink bug family - Alejandro Otero-Bravo (Nature Portfolio, 2021)
Abstract Nutritional symbioses between bacteria and insects are prevalent and diverse, allowing insects to expand their feeding strategies and niches. A common consequence of long-term associations is a considerable reduction in symbiont genome size likely influenced by the radical shift in selective pressures as a result of the less variable environment within the host. While several of these cases can be found across distinct insect species, most examples provide a limited view of a single or few stages of the process of genome reduction. Stink bugs (Pentatomidae) contain inherited gamma-proteobacterial symbionts in a modified organ in their midgut and are an example of a long-term nutritional symbiosis, but multiple cases of new symbiont acquisition throughout the history of the family have been described. We sequenced the genomes of 11 symbionts of stink bugs with sizes that ranged from equal to those of their free-living relatives to less than 20%. Comparative genomics of these and previously sequenced symbionts revealed initial stages of genome reduction including an initial pseudogenization before genome reduction, followed by multiple stages of progressive degeneration of existing metabolic pathways likely to impact host interactions such as cell wall component biosynthesis. Amino acid biosynthesis pathways were retained in a similar manner as in other nutritional symbionts. Stink bug symbionts display convergent genome reduction events showing progressive changes from a free-living bacterium to a host-dependent symbiont. This system can therefore be used to study convergent genome evolution of symbiosis at a scale not previously available.